The hell-fire clubs : sex, Satanism and secret societies - Lord, Evelyn (Yale University Press, 2008)
Lord sets aside the gossip about the Hell-Fire Clubs-- orgies, prostitutes, erotica, extreme initiation ceremonies-- in order to paint an accurate portrait of their membership, their beliefs and activities, and the reasons for their proliferation.